Verbal Competitions in the Uzbek and Russian Folkloric Traditions: Origins, Life Conditions, and Typological Features (Universal International Scientific Journal, 2026)
This article examines the origins and conditions of verbal competition genres in the Uzbek and Russian folklore traditions. It analyzes the dialogic and improvisational forms of ritual poetry, represented by the genres of olan, lapar, and chastushka. Particular attention is paid to the socio-educational, communicative, and regulatory functions of verbal duels in oral culture. Based on a comparative analysis, common typological features of these genres are identified, as well as their nationally specific characteristics. It is shown that the competitive principle, public performance, and dialogic structure are stable genre-defining characteristics of verbal competitions.
Keywords: verbal competitions; olan; lapar